Advances in the Microbial Synthesis of 5-Hydroxytryptophan - Liu, Xin-Xin; Zhang, Bin; Ai, Lian-Zhong (Frontiers in Bioengineering and Biotechnology, 2021)
5-hydroxytryptophan (5-HTP) plays an important role in the regulation of emotion, behavior, sleep, pain, body temperature and other physiological functions, and has been used in the treatment of depression, insomnia, migraine and other diseases. Due to the lack of effective biosynthesis methods, 5-HTP is mainly obtained by natural extraction, which has been unable to meet the needs of the market. Through the directed evolution of enzyme and the introduction of substrate supply pathway, the biosynthesis and yield increase of 5-HTP was realized. This paper gives examples to illustrate the production mode of 5-HTP and the latest progress in microbial synthesis.